Improving the well-being of men by Evaluating and Addressing the Gastrointestinal Late Effects (EAGLE) of radical treatment for prostate cancer: study protocol for a mixed-method implementation project. Issue 10 (3rd October 2016) - Taylor, Sophia; Demeyin, Weyinmi; Muls, Ann; Ferguson, Catherine; Farnell, Damian J J; Cohen, David; Andreyev, Jervoise; Green, John; Smith, Lesley; Ahmedzai, Sam; Pickett, Sara; Nelson, Annmarie; et al.
Abstract : Introduction: Radiotherapy treatment for prostate cancer can cause bowel problems, which may lead to severe difficulties for cancer survivors including limiting travel, work or socialising. These symptoms can appear at any time following radiotherapy. This study focuses on the early identification and protocol-based management of effects known to cause long-term, or even permanent, changes to the well-being of prostate cancer survivors. The rationale of this study is to improve the care offered to men and their families following pelvic radiotherapy for prostate cancer. Method and analysis: Implementation research methodology will be used to adopt a multicomponent intervention at three UK centres. The intervention package comprises a standardised clinical assessment of relevant symptoms in oncology outpatient clinics and rapid referral to an enhanced gastroenterological service for patients identified with bowel problems. Gastroenterology staff will be trained to use an expert-practice algorithm of targeted gastroenterology investigations and treatments. The evaluation of the intervention and its embedding within local practices will be conducted using a mixed-methods design. The effect of the new service will be measured in terms of the following outcomes: acceptability to staff and patients; quality of life; symptom control and cost-effectiveness. Data collection will take place at baseline, 6 months (±2 months), and 12 months (±2 months) after entry into the study. Ethics and dissemination: The study has ethical approval from the North West-Liverpool East Research Ethics Committee and the appropriate NHS governance clearance. All participants provide written informed consent. The study team aim to publish the results of the study in peer-reviewed journals as well as at national and international conferences. Trial registration number: UKCRN16974